RedDots: limits on habitable and undetected planets orbiting nearby stars GJ 832, GJ 674, and Ross 128 - Liebing, Florian; Jeffers, S. V.; Gorrini, P.; Haswell, C. A.; Dreizler, S.; Barnes, J. R.; Hartogh, C.; Koseleva, V.; Sordo, F. Del; Amado, P. J.; Caballero, J. A.; López-González, M. J.; et al. (Astronomy and astrophysics, 2024)
Context. The nearby (d < 5 pc) M dwarfs GJ 832, GJ 674, and Ross 128 each host a single exoplanet, with Ross 128 b located within the optimistic habitable zone. Due to their low mass and close proximity, these three systems are prime candidates for further characterization studies. Aims. Using HARPS spectroscopic data obtained by the RedDots campaign, as well as archival data from HARPS and CARMENES, supplemented with ASH2 and T90 photometry, we aim to search for additional planets in the three systems. We also aim to determine limits on possible undetected, habitable planets. We investigate (i) the reliability of the recovered orbital eccentricities and (ii) the reliability of Bayesian evidence as a diagnostic for selecting the best model. Methods. We employed Markov-chain Monte Carlo, nested sampling, and Gaussian process (GP) analyses to fit a total of 20 different models comprising 0-2 Keplerian signals and three different GP kernels for stellar activity. We used the residuals to create grids for injection-recovery simulations to obtain detection limits on potentially undiscovered planets. Results. Our refined orbital elements for GJ 832 b, GJ 674 b, and Ross 128 b confirm (GJ 832, GJ 674) or increase (Ross 128) prior eccentricity determinations. No additional planets were found in any of the systems. The detection limits obtained for all three systems are between 30 and 50 cm −1 for orbital periods in the range of 1-10 000 days. This corresponds to habitable planet masses of <1.5M⊕ for GJ 832 and < 1M⊕ for GJ 674 and Ross 128. Using N-body simulations, we find that undiscovered secondary planets are unlikely (Ross 128) or incapable (GJ 674) of having caused the observed eccentricities of the known planets. We find that the eccentricity of GJ 832b is not significantly different from zero. Conclusions. GJ 832 b, GJ 674 b, and Ross 128 b retain their status as hosting lonely and (for the latter two) eccentric planets (e = 0.04, 0.24, 0.21; respectively). This is unexpected in classical planet formation scenarios, which favor circular orbits and multiplanet configurations, demonstrating that planet formation in these cases is more complicated than traditionally thought. Additionally, the eccentricity of Ross 128 indicates that it spends some of its orbit outside of the optimistic habitable zone. Finally, our results show that Bayesian evidence, when used in conjunction with GP, is not a robust diagnostic for selecting the best model in cases of low- activity stars. In such cases, we advise an inspection of the shapes of the posterior distributions and to ensure that relevant simulations are performed to assess the validity of the perceived best model.